Study of the Dietary Preferences and the Social-Psychological Factors that Affect the Dietary Behaviors of High School and University Students - KASAMAKI, Junichi (Nippon Eiseigaku Zasshi (Japanese Journal of Hygiene), 2013)
Objectives: This study was conducted to elucidate the correlation among dietary intake, dietary preferences, and social-psychological factors in the youth and to examine the factors that affect such dietary behaviors as snacking, skipping breakfast, and taking a biased nutrition. Methods: A survey was carried out using a questionnaire with closed questions on multiple items such as dietary behaviors, psychosocial stress, dietary externalization, information and consciousness about health. The survey was conducted on 1,056 high school students and 1,323 university students in Japan. Results: As a result of the factor analysis among the groups of male/female and high school/university students, relationships were found between the items of “preferences for snacking” and “snack food intakes” among all these groups. Those who like sweets and snacks tended to snack between lunch and dinner or after dinner by themselves more often than those who do not. In contrast to men, intermediate correlations were found between the item of “a meal as a diversion” and each of the items of “snack food intake,” “preferences for fried foods/sautéed foods/meat dishes,” and “preferences for snacking,” among women who do not live alone, regardless of their being high school or university students. The item of “stress over human relationships/academic performance” was shown to have similarly weak correlations with the items of “reasons for skipping breakfast” and “nutrition intake” in the groups of male and female high school students. The less they value nutrition intake, the more they tend to be conscious of stress over human relationships/academic performance.